2019
DOI: 10.3390/ijms20122864
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Biosurfactant Complexes Characterization: Binding, Self-Assembly and Interaction with Bovine Serum Albumin

Abstract: Studies on the specific and nonspecific interactions of biosurfactants with proteins are broadly relevant given the potential applications of biosurfactant/protein systems in pharmaceutics and cosmetics. The aim of this study was to evaluate the interactions of divalent counterions with the biomolecular anionic biosurfactant surfactin-C15 through molecular modeling, surface tension and dynamic light scattering (DLS), with a specific focus on its effects on biotherapeutic formulations. The conformational analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…In brief, surfactin was isolated and purified by acid precipitation [60], namely using 6 M HCl until the pH = 2.0, and kept at 4 • C overnight. Afterward, the crude biosurfactant was pelleted by centrifugation at 9500× g for 20 min at 4 • C. Subsequently, the partially purified pellet was dissolved in deionized water, and the pH was adjusted to 7.0 using concentrated NaOH.…”
Section: Surfactin Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, surfactin was isolated and purified by acid precipitation [60], namely using 6 M HCl until the pH = 2.0, and kept at 4 • C overnight. Afterward, the crude biosurfactant was pelleted by centrifugation at 9500× g for 20 min at 4 • C. Subsequently, the partially purified pellet was dissolved in deionized water, and the pH was adjusted to 7.0 using concentrated NaOH.…”
Section: Surfactin Recoverymentioning
confidence: 99%
“…Surfactin stability was evaluated in a wide range of pH, temperatures and salinities, according to a previous report [61]. For the pH stability analysis, the biosurfactant solution (50 mg/L) was incubated at different pHs (2,4,6,8,10,12) at 20 • C. In turn, to investigate the temperature stability of the biosurfactant, its solution was incubated at different temperatures (20,40,60, 80 and 100 • C) at pH 6.0. Furthermore, the effect of the different salinity on surfactin activity was investigated in the range of sodium chloride concentrations from 2 to 12% (w/v) at pH 6.0 at 20 • C. All samples were kept at the defined temperature, pH and salinities for 2 h. The ST of each sample was determined as described above, and all measurements were performed in three independent experiments performed in triplicate.…”
Section: Surfactin Stabilitymentioning
confidence: 99%
“…We hypothesize that surfactin binds to Cu 2+ ions, mimicking copper deprivation. A previous study showed that Cu 2+ ions preferentially bind to amide nitrogens of lipopeptide biosurfactants such as B. subtilis -derived surfactin (53).…”
Section: Discussionmentioning
confidence: 99%
“…e displacement assay was done using EtBr bound CT-DNA solution (EtBr � 10 µM and DNA � 100 µM) acting as a probe. e EtBr emission intensity was increased, 98.17 90.66 (7) when it was intercalated into DNA base pairs and the emission wavelength was 601 nm (Figure 5). In addition, by increasing the concentration of complexes (0-100 µM) gradually to EtBr-DNA, the fluorescent intensity decreased due to the displacement of EtBr by complexes [63][64][65].…”
Section: Fluorescence Studies Of Competitive Displacementmentioning
confidence: 99%
“…Because of its capacity to bind reversibly to a wide range of molecules, it is considered the major transporter of regulatory mediators, metabolic products, nutrients, and fatty acids. Through hydrogen bonding, hydrophobic, and electrostatic interactions, serum albumin neutralizes endogenous and external poisons [ 7 , 8 ]. Several metal complexes are known to exert their anticancer action through effective binding with nucleases and proteins.…”
Section: Introductionmentioning
confidence: 99%